Framing Violence against Housemaids in Pakistani Print Media: A Content Analysis of Daily Jang and Dunya News - Kiran Hamid; Intikhab Alam (Review Journal of Social Psychology & Social Works, 2025)
This study explores the framing of violence against housemaids in two prominent Pakistani newspapers, Daily Jang and Dunya News, using content analysis guided by framing theory. The objective was to analyze the depiction of violence against housemaids and assess the impact of these portrayals on public perception and policy discussions. A comprehensive review of articles published over the year 2023 identified predominant frames, including responsibility and human interest, which were quantitatively analyzed to determine their frequency and context. The analysis revealed that both newspapers frequently employ the responsibility frame, with Daily Jang using it in 94.77% of articles and Dunya News in 92.31%, underscoring a narrative focus on accountability. The human interest frame was also significantly utilized, present in 85.33% of reports in Daily Jang and 61.54% in Dunya News, which personalizes the plight of the victims and elicits empathy from readers. A chi-square test was conducted to compare the reporting frequency of violence between the two newspapers, yielding a chi-square value of 0.059 with a p-value of 0.808, indicating no significant difference in the reporting frequency on this issue between the two outlets. These findings suggest that the use of specific frames potentially guides public opinion towards recognizing the severity of the issue and supporting legislative and social reforms. The study concludes that media framing in Daily Jang and Dunya News significantly shapes the discourse surrounding violence against housemaids, influencing both public perception and policy formulation. The responsible use of framing in media reporting can thus play a critical role in advocating for the rights and protection of housemaids, emphasizing the need for ethical journalism that contributes to societal change.